Streamlike function formulation of entry flow - Darus, Amer Nordin (Faculty of Mechanical Engineering, 2000)
A numerical study of fluid flow in a rectangular duct is presented. The flow of the working fluid is assumed to be steady and laminar. It is also assumed that the flow field is rotational. The flow analysis is carried out in three dimensional space using Cartesian coordinate. The problem formulation results in a non-linear type partial differential equation for the through flow velocity, which is solved numerically using marching technique. The other formulation is an elliptic type partial differential equation, for which the streamlike function is solved using successive over relaxation method. The results obtained are investigated to determine the velocity distribution across a constant duct cross section and the development of through flow velocity in the duct.